T-cell antigens of Mycobacterium immunogenum, an etiological agent of occupational hypersensitivity pneumonitis. (July 2016) - Chandra, Harish; Yadav, Jagjit S.
Highlights: This is the first identification of specific T-cell antigens (and epitopes) of Mycobacterium immunogenum (MI), an emerging pathogen associated with hypersensitivity pneumonitis (HP). Of the five recombinant MI antigens found reactive with HP patient sera, two (antigen A and antigen D) showed T-cell immune response in mouse spleen-and human blood- T cells. Immuno-informatic analysis predicted these MI T-cell antigens to bind HLA-1 and HLA-II type alleles more efficiently, with higher total human population coverage, than the widely studied reference TB antigens ESAT6 and CFP10. The identified T-cell antigens of the HP etiological agent open new avenues for development of clinical diagnostic and therapeutic and/or vaccine strategies for this difficult-to-diagnose and treat occupational lung disease. Abstract: The T lymphocyte-mediated immune lung disease hypersensitivity pneumonitis (HP) in machinists is poorly understood for disease mechanisms and diagnosis due in part to lack of information on causative T-cell antigens of the etiological agent Mycobacterium immunogenum (MI). Therefore, overall objective of the current study was to identify T-cell reactive antigens of this recently recognized pathogen. In this direction, purified recombinant form of five of the seroreactive proteins (reported in our initial study), including three cell wall-associated (arbitrarily designated as antigens A through C) and two secretory (AgD & AgE), were examined for their potential to activate antigen-presenting cells (APCs) viz. alveolar macrophages and human monocyte-derived dendritic cells (DCs) and for T-cell reactivity. All five proteins strongly activated APCs by inducing inflammatory cytokines (TNF-α, IL-6 & IL-1α) and nitric oxide (NO), albeit to a varying extent (AgE ≥ AgD > AgB ≥ AgA ≥ AgC), implying their differential potential for activation of APCs. However, only two of the five proteins (AgA, AgD) showed significant T-cell response (T lymphocyte proliferation and IFN-γ secretion) when tested using sensitized T-cells from MI-induced HP mouse model. These antigens also activated the human naïve CD4 + T cells in presence of autologous DCs as measured using ELISPOT for IFN-γ. Immuno-informatic analysis predicted that the identified T-cell antigens (AgA and AgD) bind more number of class I and class II HLA alleles as compared with the reference immuno-dominant antigens ESAT-6 and CFP-10 from the tuberculous mycobacterial species M. tuberculosis . Predicted human population coverage for the epitopes of AgA (90.87%) and AgD (88.09%) was also higher as compared to those for the reference antigens ESAT-6 (82.42%) and CFP-10 (80.21%). These two antigens were further predicted to be highly immunogenic for class I peptide MHC (pMHC) complex as compared to the reference antigens. Collectively, our results imply that AgA and AgD are T-cell antigens with a high HLA binding frequency as well as population coverage for HLA alleles. This first report on T-cell antigens and epitopes of M. immunogenum is significant as it is expected to open up avenues for understanding pathogenesis mechanisms and developing T-cell-based immunodiagnostic tools for this poorly investigated occupational lung disease.